LVM Assessed by Echocardiography and Cardiac Magnetic Resonance, Cardiovascular Outcomes, and Medical Practice - Armstrong, Anderson C. (2012)
We investigate three important areas related to the clinical use of LVM (LVM): accuracy of assessments by echocardiography and cardiac magnetic resonance (CMR), the ability to predict cardiovascular outcomes, and the comparative value of different indexing methods. The recommended formula for echocardiographic estimation of LVM uses linear measurements and is based on the assumption of the left ventricle as a prolate ellipsoid of revolution. CMR permits a modeling of the left ventricle free of cardiac geometric assumptions or acoustic window dependency, showing better accuracy and reproducibility. However, echocardiography has lower cost, easier availability, and better tolerability. From the Medline database, 26 longitudinal echocardiographic studies and 5 CMR studies, investigating LVM or LV hypertrophy as predictors of death or major cardiovascular outcomes, were identified. LVM and LV hypertrophy were reliable cardiovascular risk predictors using both modalities. However, no study directly compared the methods for the ability to predict events, agreement in hypertrophy classification, or performance in cardiovascular risk reclassification. Indexing LVM to BSA was the earliest normalization process used, but it seems to underestimate the prevalence of hypertrophy in obese and overweight subjects. Dividing LVM by height to 1.7 or 2.7 as allometric powers are the most promising normalization methods in terms of practicality and usefulness from a clinical ans scientific standpoints for scaling myocardial mass to body size. The measurement of LVM, calculation of LVMi, and classification for LVH should be standardized by scientific societies across measurement techniques and adopted by clinicians in risk stratification and therapeutic decision.